Religi Masyarakat Periferi: Analisis Rites of Passage Atas Ruwatan Rambut Gimbal di Dieng - Hamsah, Ustadi (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2020)
This article aims to see the traditions associated with the existence of the Absolute which will give birth to a unique and distinctive ritual system in the ritual of ruwatan dreadlocks in Dieng. Perception of myths and cultural phenomena with a sublimated perspective and is an innovation for the central tradition in the Ngayogyokarto Hadiningrat Palace. There was a